The needle percentage in the leafy shoot biomass of Scots pine in climate gradients of Eurasia - Vladimir Usoltsev; Walery Zukow; Ivan Tsepordey (Kazimierz Wielki University, 2022)
The efficiency of using photosynthetically active radiation by trees largely depends on the architecture of the assimilation apparatus in their crown. It is known that an increase in the level of atmospheric pollution is accompanied, on the one hand, by an increase in the foliage density on the leafy shoot length, and on the other hand, by an increase in the transparency of the crown due to the expansion of the leafless inner part of the crown. On this basis, we assume that the foliage percentage of leafy shoots (PL) is a sensitive indicator of changes in growing conditions not only due to environmental pollution, but also in broader ecological aspects, in particular, in the geographical or climatic gradients of Eurasia. For this purpose, a database of empirical data has been formed in the amount of 558 model trees of Scots pine of natural and artificial origin from 6 regions of Northern Eurasia with a measured percentage of needle in the leafy shoot biomass. A regression model has been designed, in which the contributions of mensuration variables (tree age and stem diameter), climatic variables (temperature and precipitation) and the origin of stands (natural and artificial) to explain the variability of the desired PL indicator are 15, 53 and 30 %, respectively. It is concluded that with a decrease in annual precipitation from 600 to 300 mm, there is an increase in PL by 0.2..0.3% for every 10 mm of annual precipitation, both in natural stands and in plantations. When the January temperature decreases from 0°C to -20 °C, PL increases by 0.8...1.0% for each 1°C. Thus, the foliage percentage of leafy shoots of Scots pine is an indicator of changes in growing conditions in the climate gradients of Eurasia.